ENHANCING STUDENTS' CONCEPTUAL UNDERSTANDING IN GEOGRAPHY USING A GUIDED INQUIRY MODEL ASSISTED BY MIND MAPPING - Sutoyo Budiharto; Yusawinur Barella; Dina Fitriana (GeoEco, 2026)
The Merdeka Curriculum positions conceptual understanding as the primary benchmark in geography assessment. However, in practice, students often struggle to grasp these concepts due to the complexity of the subject matter. This study aims to describe the improvement of students' conceptual understanding through the implementation of the guided inquiry learning model assisted by mind mapping. This study is a Classroom Action Research (CAR) conducted in two cycles, each comprising planning, action, observation, and reflection phases. The research was carried out at MAN 1 Pontianak, employing a purposive sampling technique to select 38 students from class XA. Data were collected using a performance assessment of mind mapping skills, operationalized through a mind mapping skill assessment rubric. The data were then analyzed using quantitative descriptive analysis. The findings indicated a significant improvement in students' conceptual understanding from Cycle 1 to Cycle 2. In Cycle 1, the average score for students' conceptual understanding reached 77.4, which fell below the school's Minimum Mastery Criterion (KKM) of 78. Following corrective actions, the average score increased to 80.2 in Cycle 2. The integration of the guided inquiry model with mind mapping proven effective in enhancing students' conceptual understanding and fostering deep, meaningful geography learning. This study offers a novel perspective on integrating guided inquiry models with concept visualization in geography education.